KORELASI ANTARA PENGEMBANGAN KARIR DENGAN MOTIVASI KERJA DAN KEINGINAN UNTUK PENSIUN DINI - Haryani, Putu Yeni (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract : Correlation Between Career Development With Work Motivation And Desire To Early Retirement. Intention to leave refers to the results of the individual intention to stay continued with in the organization, but has not been manifested in concrete actions to leave the organization. This study aimed to determine the correlation among career development with work motivation and intention to leave the organization. Using a sample of 120 employees, the data were collected using questionnaires. Furthermore, this research using Structural Equation Modelling to analyzed the data.The results of the research showed that the career development significant positive effect on job motivation and a significant negative effect on intention to leave the organization. Further, work motivation significantly negative effect on intention to leave. The findings uncovered that for those who dominated by needs for satisfying basic necessities their intention to leave is lower than those who dominated by needs for satisfying self development. The recommend of this research, the organization must be control potencial employees intention and more transparent employee career development.
Keywords: career development, work motivation, intention to leave